Evaluation of some chemical insecticides on fall armyworm attacking sweet corn - Moon, Tasfia Tasnim; Miah, Md Ramiz Uddin; Islam, Md Tofazzal; Amin, Md Ruhul (Annals of Bangladesh Agriculture, 2025)
The fall armyworm (Spodoptera frugiperda) presents a significant threat to corn production in Bangladesh, resulting in considerable yield losses. This study aimed to evaluate the effectiveness of commonly used synthetic insecticides-Winmax 40 WG (Emamectin benzoate), Ripcord 10 EC (Cypermethrin), Marshal 20 EC (Carbosulfan), and Shobicron 425 EC (Profenofos and Cypermethrin)-in managing fall armyworm infestations in sweet corn (variety BU Sweet Corn 1) at the experimental field of Bangabandhu Sheikh Mujibur Rahman Agricultural University in Gazipur, Bangladesh, during the Rabi and Kharif seasons of 2022 and 2023. In the Rabi season, leaf infestations ranged from 0.2 to 5.4%, while cob infestations varied from 5.0 to 20.0%. Conversely, in the Kharif season, leaf infestations spiked between 42.8% and 78.8%, and cob infestations ranged from 40.0 to 90.0%. The application of all insecticides significantly reduced leaf and cob infestations, along with fall armyworm larval populations, compared to the control treatment in both seasons. Specifically, Shobicron 425 EC and Marshal 20 EC demonstrated notable effectiveness in reducing infestation levels. Notably, Shobicron 425 EC treatment resulted in the highest cob length (16.4 cm in Rabi and 11.9 cm in Kharif), cob diameter (4.0 cm and 2.1 cm, respectively), cob weight (196.6 g and 80.3 g), grains per cob (537.2 and 98.0), and overall yield (12.7 t/ha and 6.2 t/ha). Collectively, the study findings indicated that the combination of Profenofos and Cypermethrin demonstrates the highest efficacy in controlling fall armyworm infestations in sweet corn under the tested field conditions. Ann. Bangladesh Agric. 28(1): 31-37